Detection of Tilapia Lake Virus (TiLV) in Tilapia (Oreochromis niloticus) by Semi-Nested Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) Method - Bimantara, Arif; Anindita, Nosa Septiana; Al Amin, Taofani Rizal; Wantonoro, Wantonoro; Setianah, Heni (International Journal of Health Science and Technology, 2023)
Tilapia productivity is influenced by many factors, one of which is Tilapia Lake Virus (TiLV) disease, which can cause a mortality rate due to infection reaching 90%. The development of nested PCR or semi-nested PCR methods can increase the sensitivity of detection of this virus. This study aims to detect the spread of TiLV attacking tilapia early using the semi-nested PCR method with primers designed in this study. Tilapia with TiLV symptoms were taken from a tilapia farmer in Sleman Regency, Yogyakarta Special Region Province. The fish is dissected, and the kidney and lymph target organs are for RNA isolation. The RNA isolation results were converted into cDNA and then amplified in two stages through the semi-nested RT-PCR method. The detection target is the third segment of the RNA of the TiLV. The first and second amplified amplicons were then electrophorized using agarose gel and observed under UV light. The detection results showed no visible band at the first amplification. In the second amplification, each sample showed positive results with the appearance of bands in the detection target gene. The semi-nested RT-PCR method is proven to increase detection sensitivity. Based on these results, it can be concluded that the semi-nested RT-PCR method in this study is effectively used to detect TiLV. It is necessary to develop research on a field scale to test the effectiveness of this method. This research is expected to provide an alternative detection of aquaculture diseases that are more effective and efficient.